Reaction of carboxylic dyes with wool and polyamide. Part III: Effect of the activating agent - Gonçalves, M. Sameiro T. (1998)
Dyes containing a carboxylic acid group had been shown to react with wool and polyamide fibres when activated with ethyl chloroformate (Parts I and II). One of the dyes, 3-aminobenzoic acid →N,N-dimethylaniline, was, in this work, activated with other chlorofirmates, so as to improve the dyeing conditions. Benzyl chloroformate was found to be a good substitute since it is not as volatile as ethyl chloroformate, which suggests that it will be easier to apply in practical dyeing conditions. The yield of the reaction with cyclohexylamine is similar to the one obtained with ethyl chloroformate, suggesting that the fixation of the dye on wool or polyamide will be much the same. The fastness results are also equivalent.